Hepatogenous Diabetes: A Comprehensive Overview - Prasetya, Ignatius Bima; Sandra, Sharon (The Indonesian Society for Digestive Endoscopy, 2025)
Cirrhosis is the advanced stage of liver disease, marked by the presence of liver fibrosis. Cirrhosis serves as a risk factor for various metabolic conditions, including hypoglycemia and hyperglycemia. Although the pathophysiology remains unclear, hyperglycemia can occur due to the interaction of various factors, such as insulin resistance. The prevalence of both diabetes mellitus and cirrhosis is increasing, and their interaction influences each other’s outcomes. Hepatogenous diabetes (HD) refers to diabetes mellitus that develops in patients with cirrhosis. HD is diagnosed using an oral glucose tolerance test, which typically reveals elevated postprandial blood glucose levels. The management of HD follows the same principles as diabetes mellitus treatment; however, pharmacological therapy should be individualized based on the patient’s liver function to ensure optimal outcome. The objective of this review is to provide a comprehensive discussion of HD, encompassing its pathophysiology, clinical implications, diagnostic approaches, and management strategies.